An Innovative Image Encryption Algorithm Based on the DNAS_box and Hyperchaos - Da Qiu; Tingting Zhang; Jingyi Liu; Song Liu; Peiyu He (Entropy)
This study proposes an innovative image encryption algorithm based on the DNAS_box and hyperchaos. The algorithm dynamically constructs a DNAS_box using 2-bit deoxyribonucleic acid (DNA) coding and 4-bit DNA-like coding, enabling seamless conversion between these two coding schemes. The implementation process comprises four key phases. First, a hyperchaotic system generates chaotic sequences while dynamically encoding the plaintext image according to DNA coding rules. Next, the 2-bit DNA keys undergo encoding before performing XOR operations with the encoded plaintext image. Subsequently, under chaotic sequence control, the DNAS_box transforms 2-bit DNA symbols into 4-bit DNA-like symbols. Finally, XOR operations are executed between the 4-bit DNA-like symbols and corresponding DNA-like keys, producing a 4-bit DNA-like symbol sequence. This sequence is dynamically decoded under chaotic sequence guidance to generate the ciphertext image. The algorithm’s effectiveness is validated through MATLAB-based numerical simulations, with experimental results confirming its robust security performance. Notably, the algorithm demonstrates a key space of approximately 10145, an NPCR exceeding 99.5%, and ciphertext entropy surpassing 7.997.